ANADOLU SELÇUKLU VE BEYLİKLER DÖNEMİNDE ÇORUM ŞEHRİ - GÖKŞEN, ALİ (Fırat Üniveristesi, 2007)
Beylikler ve Anadolu Selçuklu Döneminde Çorum şehri ve çevresi sosyal, kültürel ve mimari olarak gelişimini sürdürmüş, bu yüzyıllar boyunca nüfus hareketleri, ilim ve fikir faaliyetleri devam etmiştir. Fakat iktisadi olarak Çorum şehri diğer Anadolu Türkmen şehirleri kadar aktif görülmemektedir

Çorum city and its environs? social, cultural and architect to development has to continued in Gavernment issues and Anatolia of the Seljuk? period. In this periods has kept on population action, science and idea activities during a lot of centuries. But Çorum city hasn?t been seen to economic as as much as the ather anatolian Turcuman cities
Çorum city in the period of commonplaces and Seljuks of Anatolians
Keywords: Tarih